1999
DOI: 10.1063/1.369703
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a coplanar-electrode plasma display panel cell. I. Basic operation

Abstract: Plasma display panels ͑PDPs͒ are a technology for large-area high-brightness flat panel displays. There is considerable interest in improving PDP efficiency by optimizing the cell design, input voltage characteristics, operating conditions and gas mixture. In this article, we report on a two-dimensional computer model for PDPs which has been used to investigate the operation of a coplanar-electrode PDP cell sustained in He/Ne/Xe gas mixtures. The plasma transport equations are implicitly integrated in time to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(109 citation statements)
references
References 42 publications
(29 reference statements)
1
106
1
1
Order By: Relevance
“…Contrary to Ref. 12, we found that the electron energy equation considerably improves the reliability of the PDP model; for the calculated discharge efficiency the difference with the local field approximation may be as large as a factor of two. The transport Eqs.…”
Section: Description Of the Modelcontrasting
confidence: 40%
“…Contrary to Ref. 12, we found that the electron energy equation considerably improves the reliability of the PDP model; for the calculated discharge efficiency the difference with the local field approximation may be as large as a factor of two. The transport Eqs.…”
Section: Description Of the Modelcontrasting
confidence: 40%
“…Since the high gas pressure enhances the excimer density, the rate of this reaction may be higher at a higher gas pressure. In addition, the third possibility is the production of electrons with medium energy via He M + He M → He + + e + He [16,17]. The rate of this reaction may become higher at a higher gas pressure because of the higher density of the metastable state (He M ).…”
Section: Discussionmentioning
confidence: 99%
“…Des recherches précédentes menées dans le cadre d'une collaboration entre le GREMI (Orléans), le CPAT ( Toulouse) et la société Aupem Sefli (Gien) ont permis de démontrer l'intérêt des mélanges à bases de gaz rares pour remplacer les dispositifs actuels d'enseignes lumineuses fonctionnant sur des décharges en vapeur de mercure. Il est apparu qu'un mélange binaire néon-xénon est un couple intéressant, compte tenu de la capacité du néon à homogénéiser la décharge, et surtout celle du xénon d'émettre intensément dans le domaine de l'ultraviolet du vide, et en particulier la raie de résonance à 147 nm (transition Xe(1s 4 )→Xe(1s 0 )), qui permet d'exciter les phosphores. De plus, il a été montré que la durée de vie d'une enseigne à base de gaz rare atteignait celle des dispositifs au mercure.…”
Section: Introductionunclassified